Reanalysis of the high energy cutoff of the 1997 Mkn 501 TeV energy spectrum - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Heinzelmann, G.; Hermann, G.; Heusler, A.; Hofmann, Werner; Kettler, J.; Kohnle, A.; Konopelko, Alexander; Kornmeyer, H.; et al. (Astronomy and astrophysics, 2001)
Data taken with the HEGRA system of imaging atmospheric Cherenkov telescopes during the 1997 flares of Markarian 501 (Mkn 501) are reanalyzed using an algorithm providing improved energy resolution. A resolution of 10% to 12% is obtained by accounting for the variation of the Cherenkov light yield with the height of the shower maximum in the atmosphere. The improved energy resolution is particularly relevant for the study of the high-energy cutoff in the spectrum, which might be caused by interactions with the intergalactic infrared background radiation. The reanalysis presented here confirms the results obtained in the previous analysis, but hints a steeper slope of the spectrum in the region around 20 TeV.